Radon concentration measurements by SSNTD from construction materials used in Ben-ghazi–Libya - S. Elyaseerya, Ibrahim; A. Husseina, Nagi; K. Abdallaa, Yasin; F. Saadb, Abdallah (Libyan Journal of Science &Technology, 2024)
Materials that are used in the construction of buildings may contain radioactive elements that lead to the emission of dangerous radioactive radon gas. Radon is an alpha emitter and therefore a source of radiation occupational dose that affects immensely the general public and their environmental living conditions. A variety of construction materials, whether local or imported, are employed in Benghazi-Libya buildings and 24 samples of these construction materials were collected and their radon gas concentrations were measured by ''Can technique'' that involves the use of CR-39 Solid State Nuclear Track Detectors, SSNTD. Standardisation procedures of CR- 39 were carried out using a specially constructed standard size emanation chamber. Measurements showed that radon concentration varied from 66.7 to 625.8 Bqm-3 which are within the acceptable level set by the ICRP.